Effect of Social Media Usage on Firm Value through Profitability and Firm Growth in the Banking Industry on Indonesia Stock Exchange - Nababan, Lambok; Sadalia, Isfenti; Amalia Fachruddin, Khaira (International Journal of Psychosocial Rehabilitation, 2020)
Firm value is the perception of investors regarding the level of success of a company or the condition of the company. A bank can increase firm value by reducing asymmetric information by giving clear signals or information to outsiders through the use of social media. The study aims to analyze the influence of the use of social media on corporate value through profitability and company growth in the banking industry. This research is quantitative descriptive research. The population used in this study is the banking industry in the Indonesia Stock Exchange with a sampling method that is the census method. This study uses secondary data and structural equation modeling, or SEM, data analysis methods with Smart PLS 3 analysis tools. The results of this study indicate that the use of social media directly has a significant positive effect on firm value in the banking industry. Meanwhile, profitability and company growth variables cannot mediate the relationship between the use of social media and firm value. The results of this study are expected to make banks more active in using social media to communicate with customers.